Effect of different treatments to bacterial canker (Clavibacter michiganensis subsp. michiganensis), bacterial speck (Pseudomonas syringae pv. tomato) in tomato, and bacterial spot (Xanthomonas campestris pv. vesicatoria) in pepper - Tóbiás, A.; Lehoczki-Tornai, J.; Szalai, Z.; Csambalik, L.; Radics, L. (International Journal of Horticultural Science, 2007)
In ecological farming systems farmers can’t use chemicals against pests. In ecological plant protection the aim is to prevent diseases; if it is not possible the use of allowed materials are permitted. Until now there haven’t been enough effective and environmental friendly materials for seed treatment in organic farming. Seed borne diseases of tomato and pepper can cause serious losses in yield, so finding appropriate inhibitors has a great importance. Different materials were tested against these bacterial strains for seed treatment in this study. In vitro trials have shown that vinegar, cider vinegar, red wine vinegar and white wine vinegar have inhibiting effect against the causative agent of bacterial canker (Clavibacter michiganensis subsp. michiganensis), bacterial speck (Pseudomonas syringae pv. tomato) of tomato. These materials also have inhibiting impact on the causative agent of bacterial spot of pepper (Xanthomonas campestris pv. vesicatoria). Seed treatment with (natural alkaline material) sodium hydrogen carbonate (NaHCO3) had no effect on the examined bacterial strains. Among examined essential oils cinnamon oil seemed to be the most effective, but all oils decreased the germination ability. Thyme and savory teas were effective against Pseudomonas syringae pv. tomato. Other examined materials had insufficient bactericide impact (sucrose, NaCI, ethanol, valerian extract, peppermint tea). The germination test has shown that examined vinegar types don’t decrease germination ability.